(untitled) (Journal of the Bangladesh Agricultural University, 2017)
The study was conducted in two districts namely Sylhet and Narsingdi to investigate the production technology of Jara and Colombolemon growers, estimate profitability and identify the constraints of Jara and Colombolemon. A total sample of 120 farmers taking 60 for Jara lemon from Sylhet and 60 for Colombolemon from Narsingdi was selected randomly for the study. Data were collected through face to face interview method by using structured questionnaire during April–May, 2016. Cost return analysis revealed that Jara and Colombolemon cultivation were profitable in the study areas. Jara lemon cultivation highest cost was estimated Tk. 413575/ha in (11–15)th year garden and lowest cost was Tk. 365777/ha in 2nd year garden. Gross return was highest in 5th year garden (Tk.1995750/ha) and lowest Tk. 975600/ha in (11–15)th year garden. The benefit cost ratio at 6.5% rate of interest was 2.85and IRR 78%. Colombo lemon cultivation highest cost was estimated Tk. 316505/ha in 4th year garden and lowest cost was Tk. 257543/ha in (11–15)th year garden. Gross return was highest Tk. 841522 in 5th year garden and lowest Tk. 413616/ha in (11–15)th year garden. The benefit cost ratio at 6.5% rate of interest was 1.81 and IRR 65%. Lack of improved production technology, poor quality saplings, insect/pest infestation, adulteration of fertilizer and insecticides and less number of export buyers were found major constraints both Jara andColombo lemon production. J. Bangladesh Agril. Univ. 15(2): 289-296, December 2017